ANALYSIS OF OPERATIONAL BARRIERS AND DEVELOPMENT STRATEGIES FOR WAITINGLIST COFFEE MSMEs IN MEDAN CITY - Erika Kristina Sibarani; Marista Suryani Sitompul; Ryndian Gusty (Fakultas Ekonomi dan Bisnis Islam IAIN Kerinci, 2026)
The purpose of this study is to examine the operational obstacles and development strategies experienced by Waitinglist Coffee, a micro, small, and medium enterprise (MSMEs) in Medan, which is one of the growing culinary businesses. The methodology used is a qualitative approach through direct interviews and field observations to obtain in-depth data on issues related to raw materials, technology, marketing, and labor. The findings of the study show that the main obstacles faced by Waitinglist Coffee include a lack of quality raw material supplies, suboptimal use of digital payment systems, and limitations in digital promotion to reach a wider market. From a human resources perspective, the challenges relate to manual employee management, which impacts work efficiency. Recommended development strategies include enhancing cooperation with local suppliers, utilizing digital technology such as cashier applications and marketing through social media, and technology-based human resource management training. This study is expected to serve as a reference for other MSMEs in the culinary sector in overcoming operational obstacles and designing sustainable development strategies amid increasingly fierce business competition.